Ways of harmonization of intellectual and emotional factors of learning in art culture lessons in secondary school (Pedagogy of Higher and Secondary Education, 2011)
In the article modern lines of teaching of art culture at the senior school are considered. The innovative technologies providing unity of influence on intellectual and emotional factors of training are selected. Forms and methods of application integrative, problem-heuristic and interactive technologies are offered.
Keywords: art education; lesson of art culture; methods of art training; innovate technologies